Informal urban citizenship in the multicultural city: Literary representations of second-generation youth in Toronto and London - Tavares, David (University of Ottawa (Canada), 2010)
This thesis studies the representation of second-generation characters (i.e. the children of immigrants) in three recent novels: What We All Long For (2005) by Dionne Brand (set in Toronto), Tourism (2006) by Nirpal Singh Dhaliwal and Londonstani (2006) by Gautam Malkani (both set in London, UK). The analysis of these novels focuses on the textual relationships established between the experience of everyday urban spaces and the production of identity among the characters. The politics that emerge from the spatial negotiation of identity depicted in the novels is taken as a point of departure for considering how the novels represent 'informal urban citizenship' among second generations in multicultural Toronto and London. The relevance of the representations identified is considered in terms of how they contribute to current scholarly debates on the politics of cultural pluralism in Canada and the UK. In this way the politics of identity in urban space are vertically connected to those surrounding diversity and difference at the national scale. Further justification for the study is offered on the basis that literary representations can contribute to the constitution of powerful socio-geographical imaginaries surrounding second generations in the multicultural city. In terms of its contributions, the thesis builds on several bodies of contemporary scholarship. First, it contributes a new thematic dimension (centred on the representation of second generations) and theoretical dimension (centred on the concept of informal urban citizenship) to recent geographical scholarship on the politics of space and identity associated with literary representations. Second, it advances the theorization of literature as an object of study for geographers. Third, it adds the perspective of representational analysis to a growing body of scholarship on the spatial dimensions of informal urban citizenship among communities of recent immigrant origin. Fourth, and finally, it furthers a geographical perspective on the politics of cultural pluralism in Canada and the UK discussed in a large, interdisciplinary body of literature.
Keywords: Geography.